PENJADWALAN PROYEK KONSTRUKSI MENGGUNAKAN CRITICAL PATH METHOD (STUDI KASUS: GEDUNG LABORATORIUM TERPADU FAKULTAS TEKNIK UNIVERSITAS JEMBER) - Ahmad Maulidi; Syamsul Arifin; Hernu Suyoso (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
In the current era, the development of construction really needs to be done by implementing quality implementation, it can be done in the continued development of the Integrated Laboratory Building, Faculty of Engineering, University of Jember, in order to know some of the work included in the critical trajectory and to know the comparison between scheduling plans made with the desire of the academic community in the completion of the development. The method applied in this research is CPM (Critical Path Method) which is very suitable in various empirical construction works. From the results of this study it was concluded that scheduling using the CPM method contained several jobs including critical trajectories, namely: preparatory work, partner work, concrete work, plastering and thread work, sound system work, fire extinguishers, sanitary and sanitary work, water installations clean, dirty water installation, sprinkler installation and roof hydrants, electrical work, lightning rod installation, and the calculation of the total normal duration using CPM method obtained the completion of the project for 123 days or 6 months, while the average desires of the academic community during 6 months 18 days.